Research on “Practice Market” Oriented Art Education Teaching System--Visual Communication Design as an Example - gao, xiang (Pacific International Journal, 2023)
With the rapid development of the market economy, higher education institutions are facing new challenges in meeting the demands for innovative and entrepreneurial abilities of higher art talents. This paper focuses on visual communication design, which requires not only the basic theoretical quality of art majors but also practical skills to meet social and market needs. Through an analysis of the current situation of visual communication design specialty, this paper identifies existing problems in teaching and proposes measures to optimize and solve these problems. By doing so, this paper aims to better strengthen the training of students majoring in visual communication design. The proposed measures include incorporating industry projects into the curriculum, enhancing practical training, and encouraging interdisciplinary collaborations. It is hoped that these measures will improve the quality of teaching and ultimately produce graduates who possess both theoretical knowledge and practical skills needed for the industry.